Dealing With Issues in Construction in the Coastal Area of Soft Clay: Solution, Strategy & Implementation - Pratikso Pratikso; Soedarsono Soedarsono (International Conference on Coastal and Delta Areas, 2017)
In this condition, cities with coastal area have soft clay soil. The main problem is that the soft clay soil has bee n suffering from great settlement due to consolidation that makes the buildings around become instable, it causes the landfill is done on the soft soil. Suppose the consolidation happens naturally as it is, it will run in a relatively longer time, years or even decades. In order to be stable, it needs longer time, as consequence, the soil is not able to be used for building to which it will give damage in term of time and finance. It is why engineering is needed to fasten the consolidation process in order to make the soft clays soil able to be used efficiently. One of particular methods to fasten the consolidation process is building vertical drain. There are many ways and materials that can be used to set up vertical drain, among which are making small holes through drilling then filling it up with porous materials such as sand and gravel stone or coir. Nowadays, new method has already been available to fasten the consolidation process by geosynthetic. It is Prevabicated Vertical Drain made of polymer material. The use of geosynthetic for vertical drain can fasten the consolidation process significantly. The speed process of consolidation depends on the types of soil and model of the vertical drain as well as the distance among holes. Vertical drain can only accelerate the settlement due to consolidation, but it does not minimize it. By applying the drain model, time for the soil settlement can possibly be arranged that makes the soil of reclamation more ready for use. Keywords: consolidation, vertical drain, goesynthetic